Targeting Feeding and Eating Behaviors: Development of the Feeding Dynamic Intervention for Caregivers of 2- to 5-Year-Old Children - Ihuoma U. Eneli; Tracy L. Tylka; Rosanna P. Watowicz; Jessica Hummel; Jan Ritter; Julie C. Lumeng (Journal of Obesity)
Targeting feeding dynamics, a concept centered on the roles and interaction of the caregiver and child in a feeding relationship, may have significant potential for obesity intervention. The aim of this paper is to describe the 3-phase development of the Feeding Dynamics Intervention (FDI), an acceptability and feasibility study on implementing the feeding dynamic roles (Study 1), development of the FDI content (Study 2), and a pilot study on use of the 6-lesson FDI to promote behaviors consistent with a feeding dynamic approach (Study 3). Sample population was mothers with young children, 2–5 years old. An effect size (Hedges’ g) greater than 0.20 was seen in more than half (57%) of maternal feeding behaviors, with the largest effect sizes (Hedges’ g≥0.8) occurring with behaviors that represent the mother adopting her roles of determining what food is served, not using food as a reward, and not controlling her child’s intake. There was a significant decline in Pressure to Eat behaviors (2.9 versus 2.2, p<0.01) and Monitoring (4.1 versus 3.5, p<0.001). The FDI emerged as an acceptable and implementable intervention. Future studies need to investigate effects of the FDI on the child’s eating behaviors, self-regulation of energy intake, and anthropometrics.